Chronic liver diseases and erectile dysfunction - Zang, Guanghui; Sun, Xv; Sun, Yufeng; Zhao, Yan; Dong, Yang; Pang, Kun; Cheng, Ping; Wang, Meng; Zheng, Yuli (Frontiers in Public Health, 2023)
Chronic liver diseases (CLDs) are characterized by progressive necrosis of hepatocytes, which leads to liver fibrosis and cirrhosis, and ultimately liver dysfunction. The statistics of 2020 shows that the number of patients with CLDs, including chronic hepatitis, fatty liver, and cirrhosis, may exceed 447 million in China. The liver is a crucial organ for the metabolism of various substances, including sex hormones and lipids. CLDs frequently result in abnormalities in the metabolism of sex hormones, glucose, and lipids, as well as mental and psychological illnesses, all of which are significant risk factors for erectile dysfunction (ED). It has been reported that the prevalence of ED in male patients with CLDs ranges from 24.6 to 85.0%. According to a survey of Caucasians, liver transplantation may improve the erectile function of CLDs patients with ED. This finding supports the link between CLDs and ED. In addition, ED is often a precursor to a variety of chronic diseases. Given this correlation and the significant prevalence of CLDs, it is important to evaluate the epidemiology, risk factors, etiology, and treatment outcomes of ED in male patients with CLDs, expecting to attract widespread attention.